Behavior for Preventing Coronavirus Disease 2019 (COVID-19) among Sekaa Teruna Teruni of Kemoning Traditional Village: Descriptive Study - Ni Made Sri Meira Utami; Wiwik Oktaviani Ni Putu; Ika Setya Purwani (KHD-Production, 2023)
The behavior of preventing the transmission of Covid-19 is an activity both observable and unobservable by human interaction with the environment related to preventing the transmission of Covid-19 which is manifested in the form of knowledge, attitudes, and actions. The research method is descriptive and quantitative with a cross-sectional approach. The sample used was 87 respondents with a simple random sampling technique. The results showed that the respondent's age was 22 years (20.7%), female gender (59.8%), education at the university (71.3%), and students (46.0%) dominated. STT knowledge was in good (94.3%), enough (3.4%), less (2.3%), STT attitude was in good (96.6%), enough (2.3%), less (1.1%), STT actions are in good (88.5%), enough (11.5%), and STT behavior is in good (96.6%), enough (1.1%), less (2.3%). The behavior of preventing the transmission of COVID-19 in STT at Kemoning Village is in a good category. The advice is that it is hoped that STT will maintain good behavior in implementing health protocols and healthy behavior in the form of preventing the transmission of Covid-19.